ALOE VERA GEL FOR STREPTOZOTOCIN INDUCED DIABETES MELLITUS IN RATS - Javed, Sobia (International Journal of Pathology, 2021)
ABSTRACT Objective: To compare anti-diabetic effects of Aloe Vera gel with hypoglycemic agent, sitagliptin on streptozotcin induced diabetic rats. Materials and Methods: Study Design: Randomized Control Trial Place and Duration of Study: The study was done in Department of Pharmacology, Islamic International Medical College, Rawalpindi in collaboration with NIH, Islamabad, Pakistan, from September 2019 to August 2020. Methodology: 40, young Sprague Dawley rats were taken and randomly divided into Group A and group B. After induction of type 2 diabetes with low dose streptozotocin, group B was subdivided with n=10 each as; GroupB1 (Diabetic Control), Group B2 (Aloe Vera gel treated), GROUP B3 (Sitagliptin treated). FBS and HbA1c measured. Statistical Analysis was done by applying SPSS version 25. One-way ANOVA test was used for assessing any difference in the mean values. Post-hoc Turkey analysis was conducted to compare any inter-group mean differences. P value of <0.05 was considered significant. Results: On completion of study, at day 60, Mean FBS of Rats in Group A was 82.40 mg/dl, B1 498.40mg/dl, B2 95.70 mg/dl, B3 93.00mg/dl; Mean HbA1 of Group A was 3.71%, B1 11.84%, B2 4.17% , B3 3.73% respectively. Rats in Group B2 and B3 had significant reduction in FBS and HbA1c levels compared to Group B1, with no statistically significant intergroup difference in Groups A, B2 and B3. Conclusion: Aloe Vera gel significantly decreased fasting blood glucose and HbA1c levels with almost similar efficacy to Sitagliptin in diabetic rats.